Ammonia leaching process for selective extraction of nickel and cobalt from polymetallic mixed hydroxide precipitate. Issue 6 (December 2022) - Hu, Xiujuan; Ma, Baozhong; He, Fei; Chen, Yongqiang; Wang, Chengyan
Abstract: Nitric acid pressure leaching process (NAPL) uses nitric acid as the leaching medium to produce cobalt and nickel raw materials. Based on the benefits of nitric acid pressure leaching process for laterite ore, this paper proposes a process of "nitric acid pressure leaching-neutralization precipitation-reductive ammonia leaching separation". Firstly, thermodynamic analysis confirmed the possibilities of nickel and cobalt leaching from ammonia solution. Then the impacts of leaching agent composition, temperature, time, and liquid-solid ratio on nickel and cobalt extraction ratios were investigated. Finally, the leaching behaviors of nickel and cobalt during ammonia leaching were investigated using the shrinking core model. In addition, the phase and morphology of the leach residue were studied using X-ray diffraction (XRD) and scanning electron microscope/energy dispersive spectrometer (SEM/EDS). The reductive ammonia leaching method for treating MHP results in high nickel and cobalt extraction ratios, good separation results, and recyclable material, all of which have significant industrial application value. Graphical Abstract: ga1 Highlights: A technology for selective extraction of nickel and cobalt from MHP was proposed. The possibility of selective extraction of nickel and cobalt by reducing ammonia leaching was evaluated. The optimal system for ammonia leaching was determined. Ammonia leaching kinetics of nickel and cobalt were studied.